(3MLjI GdHUeI GdhQGKjI aj GdEKHGJ GdLfGFj (B/ s - (3SGde NejS Ydj GdXfMGfj s; (3YeQ eMeO eMeO SGde s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2012)
(3gOaJ GdOQGSI JhVjM eQGMd GdJWhQ GdJGQjNj dhSGFd GdEKHGJ GdLfGFj hUhdB ddHUeI GdhQGKjI (B: (3h cPdc HjGf eejRGJ GdHUeI GdhQGKjI h YjhHgG h WHjYJgG GdbGfhfjI(B. (3h CjVB HjGf MOhO OhQ GdHUeI GdhQGKjI (BDNA (3aj JMOjO ghjI GdBKGQ GdeGOjI GdHjhdhLjI GdeJNdaI aj eSQM GdMGOK (B: (3h cPdc JMOjO GdEWGQ GdbGfhfj ddOdjd GdeSJeO ef GdHUeI GdhQGKjI h eOi bWYjI OdGdJgG aj GdEKHGJ GdLfGFj h LGAJ GdQSGdI aj KdGKI aUhd jSHbgG aUd JegjOjs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFis
(3HHdjhLQGajG(B: (3UaMGJ (B238-255s
Keywords: (3GdHUeI GdhQGKjIs; (3GdEKHGJ GdLfGFj s; (3GdejJhchfOQjGs; (3GdJaGYd GdJSdSdj GdeHdeQ s; D.N.A; (3GdHUeI GdhQGKjI hbGfhf GdGMhGd GdGeGQGJjs; (3GdHUeI GdhQGKjI h LQGFe GdbJds; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs